2019
DOI: 10.22435/jki.v9i2.1930
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antioksidan serta Penghambatan HMG CoA dan Lipase dari Kombinasi Ekstrak Daun Binahong-Rimpang Temu Lawak

Abstract: The prevalence of dyslipidemia in Indonesia continues to increase. Free radicals are increasing the occurrence of diseases, one of them is dyslipidemia. Previous studies showed that antioxidant compounds have strong potential as dyslipidemia drug. The mechanism action of dyslipidemia treatment is inhibiting cholesterol synthesis through the HMG CoA reductase and cholesterol absorption mediated with lipase. This study aimed to analyze the antioxidant activity along with the inhibition of HMG CoA reductase and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
0
6
0
5
Order By: Relevance
“…The extract from the leaves of binahong (Anredera cordifolia (Ten) Steenis) is known to contain flavonoids that have antioxidant activity ward off free radicals. 6 A dose of 150 mg/kg BW binahong leaf ethanolic extract improved renal function in gentamicin-piroxicam-induced renal disease model rats in previous research. The current study aims to determine the impact of binahong leaves against chronic kidney damage in Sprague Dawley rats using unilateral ureteral obstruction rats model.…”
Section: Introductionmentioning
confidence: 78%
“…The extract from the leaves of binahong (Anredera cordifolia (Ten) Steenis) is known to contain flavonoids that have antioxidant activity ward off free radicals. 6 A dose of 150 mg/kg BW binahong leaf ethanolic extract improved renal function in gentamicin-piroxicam-induced renal disease model rats in previous research. The current study aims to determine the impact of binahong leaves against chronic kidney damage in Sprague Dawley rats using unilateral ureteral obstruction rats model.…”
Section: Introductionmentioning
confidence: 78%
“…The IC 50 value indicates the potential for inhibition of the HMG-CoA reductase enzyme, where the smaller the IC 50 value, the greater the inhibition potential for the activity of the HMG-CoA reductase enzyme [ 48 ]. In vitro testing using the HMG-CoA reductase assay kit showed that the ethanol extract from Tacca tubers acted as an inhibitor of HMG-CoA reductase with an IC 50 value of 4.92 ppm, which was close to the IC 50 value of simvastatin by comparison (4.62 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…This drug is an option for treating hyperlipidemia, which has a mechanism of action as an inhibitor of the HMG-CoA reductase enzyme. 14 The mechanism of action in the body by inhibiting 3-hydroxy-3-methylglutaryl HMG-CoA reductase is also responsible for converting HMG-CoA into mevalonate. In the process, it will reduce LDL by 50% and triglyceride levels in the blood.…”
Section: Discussionmentioning
confidence: 99%